Gastronomy and Neurolinguistics - Lindayani, Lilik Rita (Indonesian Journal of Multidisciplinary Scientific Studies, 2025)
This study explores the relationship between gastronomy and neurolinguistics through the perspective of gastrolinguistics, a field that examines the connection between language, taste, and human sensory experience. Gastronomy is not only understood as the art and science of eating but also as a cultural symbol system reflecting identity and collective emotion. Meanwhile, neurolinguistics investigates how the brain processes language and taste perception simultaneously. The activation of brain areas such as the insula, orbitofrontal cortex, and amygdala demonstrates that food-related words “savory,” “sour,” “sweet” can evoke neural responses similar to actual eating experiences. The concept of embodied cognition explains that the understanding of culinary language is formed through bodily experiences and episodic memory. Culinary language, idioms, and metaphors such as “the bitterness of life” or “sweet memories” illustrate the interconnection between sensory perception and emotion. This study emphasizes that the lexicon of food is not cognitively neutral but rooted in sensory and cultural experiences. Through the integration of linguistics, culture, and neuroscience, this research contributes to a new understanding of how humans construct the meaning of taste through language and how language itself can stimulate taste-related experiences at the neurological level.